Characteristics of unclaimed prescriptions in a college-aged population. Issue 1 (14th February 2022) - Davis, Jennifer L; Carpenter, Sierra; Irwin, Adriane N
Abstract: Objective: Describe the frequency and characteristics of unclaimed prescriptions from a pharmacy embedded within a student health services clinic. Methods: Cross-sectional study of prescriptions received by an on-campus pharmacy between September 1–December 31, 2017 and September 1–December 31, 2018. Prescription data were extracted from the pharmacy administrative database and then categorized into medication classes and claimed versus unclaimed. Results: The pharmacy received 18, 337 prescriptions during the study periods. Medications classified as central nervous system (n = 5101, 27.8%), hormones (n = 3976; 21.7%), and anti-infective (n = 3262, 17.8%) medications were most common. A total of 2, 609 prescriptions (14.2%) were left unclaimed by patients. The frequency of unclaimed prescriptions varied across medication classes, ranging from 9.0% (anti-infective) to 34.1% (genitourinary). Conclusions: Approximately one in seven prescriptions went unclaimed at this on-campus pharmacy. Future research is needed to identify predictors for unclaimed prescriptions to develop effective interventions that improve medication adherence.